2017
DOI: 10.1002/jctb.5185
|View full text |Cite
|
Sign up to set email alerts
|

Microbial lipid production from lignocellulosic hydrolyzates: effect of carbohydrate mixtures and acid‐hydrolysis byproducts on cell growth and lipid production by Lipomyces starkeyi

Abstract: BACKGROUND The effects of byproducts of lignocellulosic hydrolyzates, such as furfural, 5‐hydroxy methyl furfural (HMF), vanillin, para‐hydroxy benzaldehyde (PHB), and syringaldehyde, on the growth and lipid accumulation by Lipomyces starkeyi were investigated. All the studies were conducted using a minimal medium. RESULTS The growth and lipid accumulation patterns on individual sugars (glucose and xylose) were similar, sequential utilization was observed when both the sugars were present in the medium. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…These furaldehydes have a negative fallout on the rate of enzymatic hydrolysis, inhibiting the enzymes used to liberate the sugars from the (hemi-)cellulose fractions [27] . They also inhibit the yeast and bacterial growth, and consequently alcohol fermentation, in a dose-dependent manner [28,29] . Large amounts of organic acids, such as acetic, formic, and levulinic acid, are contained in pretreated lignocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…These furaldehydes have a negative fallout on the rate of enzymatic hydrolysis, inhibiting the enzymes used to liberate the sugars from the (hemi-)cellulose fractions [27] . They also inhibit the yeast and bacterial growth, and consequently alcohol fermentation, in a dose-dependent manner [28,29] . Large amounts of organic acids, such as acetic, formic, and levulinic acid, are contained in pretreated lignocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Beckmann et al 38 applied full factorial design of experiments to optimize the concentration of glucose and leucine in the feed medium and achieved a cell density of 97 g L -1 for the leucine auxotrophic E. coli strain K12 ER2507. Subramaniam et al [48][49][50] developed a mi nimal medium by replacing costly yeast extract with vitamins such as biotin, calcium pantothenol and inositol. They utilized RSM to optimize the concentrations of vitamins and phosphates.…”
Section: Cell Growth and Medium Optimizationmentioning
confidence: 99%
“…They utilized RSM to optimize the concentrations of vitamins and phosphates. With the optimized minimal medium, Subramaniam et al [48][49][50] could reduce the medium cost for lipid production by Lipomyces starkeyi from $12.68 per gallon lipids to $3.11 per gallon lipids with high cell density of 44.5 g L -1 and lipid concentration of 33.5 g L -1 .…”
Section: Cell Growth and Medium Optimizationmentioning
confidence: 99%
“…Furthermore, a previous study has shown that the residual glycerol up to 5% did not inhibit cellulosic ethanol production by Saccharomyces cerevisiae following pretreatment of sugarcane bagasse [6]. Nevertheless, besides glycerol, biomass degradation and hydrolysis products, such as soluble phenolics from lignin and furans from sugars in the residual pretreatment hydrolysate, may also have inhibitory effects on microorganisms [9][10][11].…”
Section: Introductionmentioning
confidence: 96%